Hubungan Patron Klien Petani Karet Dengan Tauke Di Kecamatan Bantan Kabupten Bengkalis - sukri aditya (Jurnal Agribisnis, 2022)
ABSTRAK The aims of this research are : (1) Knowing the characteristics of Tauke and rubber farmers in Bantan district, Bengkalis regency, (2) Analyzing the relationship between Tauke and rubber farmers in Bantan district, Bengkalis regency.This research was conducted in Bantan district Bengkalis regency, this research was conducted in 2019 to 2020. The sampling technique that will be used in this research is purposive sampling method. The total sample taken was 78 samples. The data analysis method used to answer the objectives in this research is descriptive.The results showed that: (1) characteristics of tauke and farmers include age, agricultural experience, number of families, land area, education and family dependents, (2) tauke relationship is seen from the existence of reciprocal relationship that is a mutually beneficial relationship, The ownership of economic resources are not balanced between farmers and rubber tauke, personal relationship is a direct and intensive relationship between patron and client, which causes the relationship to occur is not solely motivated by profit alone , but also contains elements of feelings that can be contained in personal relationships, and loyalty relationships (loyalty or obedience).